2018
DOI: 10.1021/acs.jpcc.8b05364
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Different Products of Nitrosobenzene and Nitrobenzene Hydrogenation on Pd(111) under Realistic Reaction Conditions

Abstract: Selective hydrogenation of nitroarene compounds is applied in many fields such as agrochemicals, pharmaceuticals, and dyes. Pd-catalyzed hydrogenation of nitrobenzene (PhNO2) and nitrosobenzene (PhNO) could exhibit different selectivities. This was regarded as the evidence to challenge the Haber mechanism for PhNO2 hydrogenation in which PhNO is an important intermediate. In this study, we systematically investigate their hydrogenation mechanisms under realistic reaction conditions based on first-principles ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…[37][38][39][40][41] Despite the relevance of the reduction of nitro compounds, only few studies on the reaction mechanism were published during the years and the majority of them dealt with heterogeneous noble metal catalysts (mainly based on Pd, Pt, Au and Rh). 17,[42][43][44] As a consequence, the mechanism reported by Haber still continues to represent the main reference for describing the possible reaction pathways, even in the case of non-noble metal catalysts. An exception is represented by Ni-based heterogeneous catalysts, for which two studies were very recently reported and will be discussed in the dedicated chapter.…”
Section: Introduction: Setting the Scenementioning
confidence: 99%
“…[37][38][39][40][41] Despite the relevance of the reduction of nitro compounds, only few studies on the reaction mechanism were published during the years and the majority of them dealt with heterogeneous noble metal catalysts (mainly based on Pd, Pt, Au and Rh). 17,[42][43][44] As a consequence, the mechanism reported by Haber still continues to represent the main reference for describing the possible reaction pathways, even in the case of non-noble metal catalysts. An exception is represented by Ni-based heterogeneous catalysts, for which two studies were very recently reported and will be discussed in the dedicated chapter.…”
Section: Introduction: Setting the Scenementioning
confidence: 99%
“…The whole reaction is exothermic (−1.85 eV), indicating that the nitrobenzene hydrogenation on the Mo 2 C/NC surface is thermodynamically favored (Table S4). Noteworthily, the whole reaction energy can even rival that for previously reported Pd(111) (−1.38 eV), revealing that the activity of Mo 2 C/NC is comparable to that of noble‐metal based catalysts in hydrogenation of nitrobenzene to aniline [40a] …”
Section: Resultsmentioning
confidence: 60%
“…The overall pathway of 4-NP reduction can be described as: C 6 H 5 NO 2 → C 6 H 5 NOOH* → C 6 H 5 NO* → C 6 H 5 NOH* → C 6 H 5 N* → C 6 H 5 NH* → C 6 H 5 NH 2 . 45,46 The reaction from the initial NO 2 − to the final NH 2 − is accompanied with a sharp 4.3 eV decline in energy. Nitrosobenzene (PhNO) is considered a key intermediate for the calculations, and the detailed results are given in the ESI (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S16-S18 †). 45 For the first stage, the energy for the adsorption (E ads ) of 4-NP on the (110) surface of CuO and OVs-CuO is −0.68 and −0.73 eV, respectively (Fig. 5b).…”
Section: Paper Nanoscalementioning
confidence: 99%
See 1 more Smart Citation